EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN KONSEP DIRI SISWA KELAS XI DI SMA NEGERI 3 MANDREHE UTARA TAHUN PELAJARAN 2023/2024 - Zebua, Meilda Kristiani (Counseling For All : Jurnal Bimbingan dan Konseling, 2024)
This study aims to describe the level of self-concept of class XI students at SMA Negeri 3 Mandrehe Utara before being given group guidance services and after being given group guidance services. Testing the effectiveness of group guidance services in improving the self-concept of class XI students at SMA Negeri 3 Mandrehe Utara. The type of research used is quantitative research with a Pre-Experiment design, namely a one group pre-test-post-test design. The research population and sample were class XI of North Mandrehe 3 Public High School, totaling 35 people. This was proven before implementation on students' concept level which was in the low category and after implementation H0 was rejected and Ha was accepted so that group guidance services were effective in increasing the self-concept of class XI students at SMA Negeri 3 Mandrehe Utara for the 2023/2024 academic year. It is recommended that students take part in group guidance service activities, providing full support to guidance and counseling teachers for the provision of guidance and counseling services by providing supporting facilities and facilities, so that students' positive self-concept can increase.